FACTORS INFLUENCING THE ADOPTION OF CABBAGE (Brassica oleraceavar. capitata) PRODUCTION TECHNOLOGIES IN JOS SOUTH AGRICULTURAL ZONE PLATEAU STATE, NIGERIA - Joel, D.; Babaji, A.U.; Muhammad, R.; Elaine, I. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the factors influencing adoption of cabbage (Brassica oleracea var. capitata) production technologies in Jos South Agricultural Zone of Plateau State, Nigeria. A multi-stage sampling technique was used to select 169 cabbage farmers from four districts (Du, Gyel, Kuru, and Vwang) and eight villages within Jos South LGA. Primary data were collected through structured questionnaires and analyzed using descriptive statistics (frequency, percentages, and means) and binary logistic regression. Findings revealed that, the mean age of respondents was 40.1 years, indicating that most farmers were within the active and productive age group, while the mean household size was 7.2 persons, suggesting availability of family labour. The average farming experience was 7.9 years, and mean annual farm income was ₦453,200, indicating moderate profitability. Extension agents were the major source of information, accounting for 35.4%, followed by fellow farmers (25.6%) and workshops/training (15.9%). The logistic regression results showed that, model was statistically significant (χ² = 68.32, p < 0.001) with a Nagelkerke R² value of 0.69, indicating that 69% of the variation in adoption was explained by the included variables. Significant determinants of adoption included education (β = 0.482, p < 0.01), access to credit (β = 0.621, p < 0.01), extension contact (β = 0.705, p < 0.001), farming experience (β = 0.298, p < 0.01), household size (β = 0.167, p < 0.05), and market access (β = 0.412, p < 0.05). Input cost (β = -0.533, p < 0.01) and climate factors (β = -0.298, p < 0.05) negatively influenced adoption. Major constraints identified included insufficient credit (mean = 4.21), inaccessibility to loans (mean = 4.20), low capital base (mean = 4.18), high cost of production (mean = 4.19), and poor storage facilities (mean = 4.10), all indicating severe financial and infrastructural challenges. The study concluded that adoption of improved cabbage production technologies is largely driven by financial capacity, institutional support and access to information. Based on the result of this study, it is recommended that strengthening extension services, improving access to affordable credit and reducing input costs to enhance adoption and productivity among cabbage farmers in the study area.